P269 Utility of capsule endoscopy in the diagnosis of inflammatory bowel disease and its disease extent. (25th January 2019) - Bong, S H S; Lee, W J; Aw, M M; Quak, S H; Goh, E J; Gowans, M; Ong, D E; Hartono, J L
Abstract: Background: Capsule endoscopy is an established non-invasive tool for the evaluation of small bowel due to its ability to visualise subtle mucosal abnormality that may not be detected by cross-sectional imaging. We aim to evaluate its utility in patients with suspected inflammatory bowel disease (IBD) and in known IBD patients in a single tertiary hospital. Methods: Retrospective analysis was done for all patients who underwent capsule endoscopy with PillCam™ SB video capsule system from the National University Hospital, Singapore from January 2006 to December 2016. Clinical data, laboratory results, and medications were assessed using electronic medical records and electronic prescription. Statistical analysis was done using SPSS. Categorical variables were compared using χ 2 test with Fisher exact test and continuous variables were compared using Student's t -test where appropriate. Results: There were 426 patients who underwent capsule endoscopy from January 2006 to December 2016. Among these, 35 (8.2%) patients underwent capsule endoscopy for suspected IBD while 16 (3.8%) patients underwent capsule endoscopy for known IBD. There were 19 (37.3%) patients in the paediatric age group and 32 (62.7%) patients in the adult age group. Thirty-one (60.7%) patients were males and 20 (39.2%) patients were females. Of the 35 patients with suspected IBD, 7 (20.0%) patients were diagnosed with IBD after capsule endoscopy was done. Suspected IBD patients who were subsequently diagnosed with IBD following capsule endoscopy had a significantly lower mean albumin level (39 ± 4.41 g/l) compared with patients who were not diagnosed with IBD (39.0 ± 4.41 g/l vs. 43.0 ± 3.28 g/l; p = 0.039), and were more likely to have hematochezia (3/7; 42.9% vs. 2/28; 7.1%, p = 0.044). There were no significant difference in haemoglobin, white cell count, C-reactive protein, creatinine, presence of diarrhoea, and weight loss, between patients who were subsequently diagnosed with IBD and those who were not. Among the 16 patients with known IBD, there was a change in IBD phenotype following capsule endoscopy in 2 (12.5%) patients, with extension of involvement from Montreal L2 (colonic) to L3 (ileocolonic) . Four (25.0%) patients had intensification of treatment following capsule endoscopy: one patient was started on biologics and 3 others were started on immunomodulators. Conclusions: Although IBD-related evaluation compromised a small proportion of overall capsule endoscopy referrals, capsule endoscopy is a useful tool in making the diagnosis of IBD, and in the evaluation of the extent of IBD, resulting in optimisation of treatment.